Heterocycles for life-sciences applications and information storage - Shrestha, Tej Bahadur (Kansas State University, 2012)
The photochromic spirodihydroindolizine/betaine (DHI/B) system has been reinvestigated applying picosecond, microsecond, stationary absorption measurements, and NMR-kinetics. The first surprise was that the electronic structure of the betaines is quite different than commonly assumed. The photochemical ring-opening of DHIs to betaines is a conrotatory 1,5 electrocyclic reaction, as picosecond absorption spectroscopy confirms. The (disrotatory) thermal ring-closing occurs from the cisoid betaine. The lifetime of the transoid betaine is 60 s at 300 K, whereas the lifetime of the cisoid isomer is of the order of 250 microseconds. According to these results, the electrocyclic back reaction of the betaines to the DHI is NOT rate determining, as previously thought, but the cisoid-transoid-isomerization of the betaine. Although the presence of a second nitrogen atom increases the photostability of the spirodihydroindolizine-pyridazine/betaine-system remarkably, the photochemical reaction mechanism appears to be exactly the same for spirodihydroindolizine-pyridazine/betaine-system. A nondestructive photoswitch or an information recording systems has been explored using styryl-quinolyldihydroindolizines. Both isomers DHI and betaine are fluorescent. When the blue betaine is stabilized in a thin polymethyl methacrylate (PMMA) matrix, it is stable for several hours even in room temperature and very stable at 77K. Although irradiation of visible light = 532 nm allows the photo-induced reaction of the Betaine back to the DHI, a nondestructive read-out can be performed at λ = 645 nm upon excitation with λ = 580 nm. Image recording (write) and read-out, as well as information storage (at 77K) have been demonstrated. Charged and maleimide-functionalized DHI/B systems have beed synthesized for use as photochemical gates of the mycobacterial channel porin MspA. Positively charged and maleimide functionalized DHI groups that were attached to the DHI/B-system permit the binding of the photoswitch to selective positions in the channel proteins due to the presence of a cysteine moiety. An inexpensive new method for the large scale synthesis of coelenterazine is developed. A modified Negishi coupling reaction is used to make pyrazine intermediates from aminopyrazine as an economical starting material. This method permits the use of up to 1g coelenterazine per kg body weight and day, which turns the renilla transfected stem cells into powerful light sources.
Keywords: Spirodihydroindolizines; Photochromic switch; MspA; Coelenterazine; Bioluminescence; Optical data storage; Chemistry (0485)